Volume dan Kapasitas Jaringan Jalan di Kawasan Pondok Labu - Said Djamaluddin; Adella Hotnyda Siregar; Pungkas Hendratmoko (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2015)
The  intent  of  this  study  to  analyze  the  optimization  of  highway  network  of  hospitals Fatmawati to Pondok Labu (UPN “Veteran“ Jakarta). Especially for measuring the ratio of the volume and capacity (V/C) of the facilities and infrastructure, given the congestion level above the tolerance within 2-3 km of the RS Fatmawati-UPN "Veteran" Jakarta, takes 2-3 hours the goal is to repair the target to be achieved to make people gain easy mobility around Pondok Labu Fatmawati according to their desired travel. Some of the recommendations suggested by research, must make a one-way flow (OWF) in the morning of Pondok Labu to Fatmawati hospital and vice versa for in the evening. Another recommendation is proposed, so that the dividing line in front of the giant malls are also eliminated, there is no parking along the road, a road equipped, disciplined pass-traffic control and also realocation Market Pondok Labu.